Development of google site-based mathematics learning media with core model for grade VIII students - Dilla, Siska Chindy; Hidayat, Wahyu (Pi Radian: Journal of Mathematics Education, 2023)
21st century learning strives for students to be able to actively construct concepts, develop their knowledge, and use ICT tools. Especially the transition from post-pandemic learning, students are required to be more independent in learning. So we need learning media that can help overcome these problems. The purpose of this research is to develop and produce a website-based learning media with the google site combined with the CORE model in mathematics learning for junior high school students in good quality statistical material by meeting the validity and feasibility criteria. The selected development model is the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The instruments used include validation questionnaires, practicality questionnaires, and learning outcomes tests.Technical analysis of the data was carried out qualitatively to measure the data descriptively and quantitatively to calculate the scores of the results of the feasibility test of the learning media that the researchers had developed. The results of the research on the development of learning media are based on the material aspect of 77,5%, the media aspect of 81%, the practicality of the learning media from the responses of students to get a percentage of 85,2% with a very decent category.After trying the learning media, students were asked to do posttest and learning questionnaires, 78,6% of students had good learning achievements.Thus, the learning media of mathematics learning media using the google site with the CORE model that the researcher developed is very suitable for use in learning.